Advances in Endoscopic Ultrasound in Pancreatic Cancer Screening, Diagnosis, and Palliative Care - Wenyu Zhang; Jingzheng Chen; Wei Zhang; Min Xu (Biomedicines)
Pancreatic cancer is a highly aggressive malignancy with a profoundly poor prognosis. Clinically, the condition most frequently manifests with symptoms including painless jaundice, abdominal discomfort, and back pain. Early diagnosis and the implementation of effective therapeutic strategies are critical for improving patient survival outcomes. However, merely 10–20% of patients are diagnosed at an early stage, with the majority presenting at advanced stages, often with metastasis. Consequently, early detection and intervention are crucial for enhancing prognosis. The widespread adoption of endoscopic ultrasonography (EUS) technology in recent years has significantly enhanced the diagnostic accuracy for pancreatic space-occupying lesions. EUS is increasingly recognized for its pivotal role in alleviating malignant biliary obstruction (MBO), gastric outlet obstruction (GOO), and refractory pain in advanced pancreatic cancer. This article aims to provide an overall review of the current applications of EUS in the diagnosis and treatment of pancreatic cancer, exploring its advantages and limitations in early screening, diagnosis, and palliative care. Furthermore, this review explores potential future directions in the field, aiming to provide valuable insights to inform and enhance the clinical management of pancreatic cancer.